Primary thyroid biphasic synovial sarcoma and synchronous papillary carcinoma: report of a remarkable case - NICOLA, M.; ONORATI, M.; BERTOLA, G.; COLLINI, P.; FASCÌ, A.I.; DI NUOVO, F. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
Synovial Sarcoma (SS) is the fourth most common soft tissue sarcoma, characterized by translocation t(X;18) (p11.2;q11.2). Although its histological features have been extensively described, this entity is characterized by a wide morphological spectrum so that the recognition can be very challenging at atypical anatomical localization, like the thyroid. We describe a case of a 42-ysold female patient complaining a cervical swelling due to left ntrathyroid nodule, measuring 35 mm in its greatest dimension. A Fine Needle Aspiration Cytology (FNAC) was performed and diagnosis of indeterminate neoplastic lesion, indefinite whether primary or metastatic, was formulated. After complete thyroidectomy, the histological picture of the nodule was characterized by a dual cellular population: several glandular structures composed by columnar cells with clear cytoplasm were embedded in a highly cellular stroma composed of spindle-shaped elements. Immunohistochemistry and molecular biology confirmed the morphological suspicion of SS identifying the fusion transcript SYT-SSX1 and thus ruling out several differential diagnoses which include more common thyroid malignancies. Moreover a synchronous papillary microcarcinoma was detected in the controlateral lobe. This case is noteworthy since it describes the synchronous presence in the thyroid of two completely different malignancies, the first one belonging to the soft tissue neoplasm category and the other one originating from the thyroid follicular epithelium.